A STUDY ON THE ISSUES AND PROBLEMS OF WOMEN ENTREPRENEURS IN KERALA WITH SPECIAL REFERENCE TO MALAPPURAM DISTRICT - P, Unnikrishnan; Bhuvaneswari, S (International Journal of Research -GRANTHAALAYAH, 2016)
The entrepreneurs play an important role in the economic and social development of the nation. Women entrepreneurs are also giving a partial role in this field. Now a day, society gives a better socio economic status to women. The State and Central Government has been introduced various schemes and empowerment programs to promote them to sustain in good working conditions of women enterprise. At present, the number of women entrepreneurs in Kerala is low. If the Government takes necessary promotional measures, the number will rise into an indefinite in future and they can contribute much for the entrepreneurial growth of Kerala. Mostly the women are producing home need items, and this type of essentials & food items. These opportunities can be further applied for the growth of Kerala’s entrepreneurship and the future of women entrepreneur will be an asset for the growth of our state. This study helps to find out the various problems faced by women Entrepreneurs in Malappuram District. The details are directly collected from women entrepreneurs to observe their problems.